2010
DOI: 10.2147/nbhiv.s13936
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in treated HIV patients

Abstract: Although highly active antiretroviral therapy (HAART) has reduced the incidence of HIV-associated dementia, the overall prevalence of HIV-associated neurocognitive disorders (HAND) has increased. Since treatment and prevention of HAND are becoming an increasing concern, management strategies for cognitive impairment in patients living with HIV are expected to play an important role in the near future. This review summarizes the existing literature on studies investigating cognitive functions in patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 75 publications
1
9
1
Order By: Relevance
“…It is not possible from existing data to conclude whether patients with successful treatment (ie, plasma HIV RNA <50 copies/ mL) are at risk of progression and there are no systematic studies addressing the extent to which neurocognitive deficit may be permanent or reversible. Data show that cART for approximately 1 year is associated with modest benefits in NP functioning, particularly attention, processing speed, and executive performance (CEBM 1a) [73][74][75][76][77]. The degree of improvement correlates with changes in CD4 + T-cell counts (CEBM 1a) [42,[78][79][80][81][82].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…It is not possible from existing data to conclude whether patients with successful treatment (ie, plasma HIV RNA <50 copies/ mL) are at risk of progression and there are no systematic studies addressing the extent to which neurocognitive deficit may be permanent or reversible. Data show that cART for approximately 1 year is associated with modest benefits in NP functioning, particularly attention, processing speed, and executive performance (CEBM 1a) [73][74][75][76][77]. The degree of improvement correlates with changes in CD4 + T-cell counts (CEBM 1a) [42,[78][79][80][81][82].…”
Section: Treatment and Preventionmentioning
confidence: 99%
“…This implies the presence of a non-reversible component of neural injury and possibly some neural injury continues in some patients regardless of the benefits of anti-retroviral therapy [46]. Notwithstanding, the evidence in support of HAART-related cognitive improvements in HIV infection is convincing enough to advocate its use in the management of HAND.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, saquinavir, the first protease inhibitor, was shown to increase the CD4 cell count and decrease the plasma viral load. 24 Further studies of cognitive function under HAART confirmed these early findings (for a review, see Tozzi et al 25 ). 22 However, resistance to each previously discovered drug developed, leading to clinical trials of 3-drug combination therapy.…”
mentioning
confidence: 87%